Stopping the Virus; Study on Participatory Journalism and Digital Humanitarian during a Non-Natural Disaster in Indonesia - Nusantara, Samiaji Bintang; Rinaldi, Ingki; Veronika, Veronika (Journalism Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, 2024)
Philanthropic initiatives during disaster events have become embedded in Indonesian society. It also manifests in a digital humanitarian practice during the COVID-19 pandemic, categorized by the government as a non-natural disaster from 2020 to 2023. The spreading of misinformation and inaccurate data on cases of COVID-19 patients, have become an obstacle in the early stages of efforts to stop fatalities. As the government imposes lockdown and restrictions access to information, the news media as one of the key sources of information is under attack. Thus, citizen initiatives in stopping the pandemic are worth documented as a lesson learned when managing disasters in the future. By conducting qualitative method, this research describes the implementation of participatory journalism in practice related to the data gathering and reporting on COVID-19 cases in Indonesia by